Mengarusutamakan Moderasi Beragama di Kalangan Remaja: Kajian Konseptual - Hadiat Hadiat; Syamsurijal Syamsurijal (Jurnal Ilmiah Wahana Pendidikan, 2021)
Teenagers are vulnerable to being exposed to the virus of intolerance and radicalism, this must be used as a study material for all parties. The purpose of this study is to describe the form of mainstreaming religious moderation among adolescents. The approach used is a qualitative approach. Its nature is natural and fundamental and oriented to natural or naturalistic phenomena or phenomena. This research method uses library research. The results of his research include: (1) religious moderation in the family is very important. The practice of moderate attitude that is highlighted by parents is part of learning by doing. (2) religious moderation in schools/madrasas is very strategic to implement. the values ​​of religious moderation are easy to apply to students, teachers are the main pioneers in internalizing the values ​​of religious moderation in subjects. (3) religious moderation on social media is very representative. The reach of socialization and internalization of the values ​​of religious moderation is not only accessible to the surrounding community, but is able to penetrate various cities, provinces and across countries.